Client-centered and Experiential Psychotherapy in the Nineties - Lietaer, G. (Studia Psychologica, 1990)
This voluminous book of 47 chapters offers a good cross section of what is burgeoing in the field of client-centered and experiential psychotherapy on the threshold of the nineties. it does not represent a single vision but gives the floor to the various suborientations: classics Rogerians; client-centered therapists who favor some form of integration or even eclecticism; experiential psychotherapists for whom Gendlin's focusing approach is a precious way of working; client-centered therapists who look at the therapy process in terms of information-processing; existentially oriented therapists... Remarkable is that - for the first time in the history of client-centered/experiential psychotherapy - the European voice rings through forcefully: more than half of the contributions were written by authors from Western Europe. Several chapters contain reflections on the evolution - past, present, and future - of client-centered/experiential psychotherapy. The intensive research into the process, which had a central place in the initial phase of client-centered therapy, is given here ample attention, with several creative studies and proposals for renewal. In numerous contributions efforts are made to build and further develop a theroy of psychopathology, the client's process, the basic attitudes and task-oriented interventions of the therapist. The chapters dealing with clinical practice typically aim at the description of therapy with specific client populations and paricularly severely disturbed clients. And finally a few fields are introduced which are new or barely explored within the client-centered/experiential approach: working with dreams, health psychology, couple and family therapy.